The concept of sanctity of life from the Islamic legal perspective - Wan Muhammad, Ramizah; Hussin, Nasimah; Jahn Kassim, Puteri Nemie (2014)
It is the conviction and belief of all Muslims that life belongs to Allah swt. Life is merely a loan until death take place. Allah swt has entrusted this loan to mankind so that His believers will worship him. The word “life” in Arabic is Hayat and in the Holy Quran, Allah swt has mentioned this word and its derivatives 193 times. This fact shows the importance of “life” and the necessity to take good care of our lives and protect the life of others. Protecting the life of others includes the life of Muslims as well as non-Muslims. In Islamic law, one of the principles in maqasid shariah is to protect one’s life. Protection of one’s life includes one has to take care of his body, his health and his mind from any kind of intervention that would lead to harm and death. The ambit of protection also includes protecting the body and limbs from being violated by others and if violated, punishments will be inflicted upon the violators. It is also permissible to defend our lives and loved ones from being violated by others. This paper seeks to look at various issues such as the concept of life and death, issues on end of life, medical intervention and duties for everyone to take care of their lives as well as the lives of others. The paper will further examine whether it is permissible to end one’s life if he is dying provided that it is done with sincerity and reasonable care upon receiving advice from the medical experts who are true believers as well as following the right procedures. The consent of family members who are legally competent will also be instrumental in deciding on issues pertaining to end of life.